Kualitas Pendidikan Islam Yang Unggul: (Kontribusi Pendidikan Karakter Sebagai Perekat Utama) - Surahman, Susilo (ALACRITY : Journal of Education, 2024)
This article discusses the important contribution of character education as the main glue in improving the quality of superior Islamic education in Indonesia. Character education is considered a fundamental aspect in shaping students as individuals with noble morals in accordance with Islamic teachings. The study highlights how the implementation of Islamic character values can enrich the educational process and provide long-term benefits to learners, educational institutions, and the wider community. Through the development of quality Islamic education that is integrated with character education, it is expected to create a conducive learning environment for students' spiritual and intellectual growth. The research methods used include a comprehensive analysis of the development of the Islamic education curriculum that integrates character education, as well as tracing the resulting positive impacts. The findings of this study provide an in-depth understanding of the relevance of character education in creating a superior generation that is not only academically intelligent, but also has noble morals in accordance with Islamic teachings. The implementation of character education as the main glue in Islamic education is a significant step in improving the quality of Islamic education in Indonesia.